2022
DOI: 10.1021/acssuschemeng.2c05264
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Thermophysical and Mechanical Properties in Hydrated Lignin with Compositions Close to Softwood

Abstract: The hydrogen bonding network analysis of softwood lignin is relevant to designing novel technologies to overcome the recalcitrance of plant biomass in the industrial deconstruction and manufacturing of ligninbased carbon fibers. In this work, we examine, by atomistic simulations, the hydrogen bonding network in guaiacyl-rich lignin and guaiacyl-type lignin over a wide range of temperatures. We determine the formation of stable water-bridged dimeric complexes by the interaction of phenolic and aliphatic hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 100 publications
(227 reference statements)
0
10
0
Order By: Relevance
“…Previous studies on lignin structures have revealed the presence of short distance ordering in the range of 4.0–4.2 and 5.3–6.1 Å considered to be related to sandwiched and T-shaped π–π stacking interactions, respectively. , Six predominant distances/sizes ( D 1 , D 2 , D 3 , D 4 , D II order3 , and D II order4 ) were observed in lignin samples by WAXS, as shown in Table and Figures S19–S24. Based on the distance within these repeating features, D 2 and D 3 can be attributed to T-shaped and sandwich π–π stacking (combined parallel displaced and cofacial parallel stacked) interactions between the abundant lignin aromatic rings. , This should however be considered a simplification due to the highly complex three-dimensional lignin network structures. These π–π stacking interactions between aromatic rings normally play an important role in the stability of the systems and their properties. ,, It is however not clear how these internal stacking interactions scale when being imbedded into a larger structural ordering.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on lignin structures have revealed the presence of short distance ordering in the range of 4.0–4.2 and 5.3–6.1 Å considered to be related to sandwiched and T-shaped π–π stacking interactions, respectively. , Six predominant distances/sizes ( D 1 , D 2 , D 3 , D 4 , D II order3 , and D II order4 ) were observed in lignin samples by WAXS, as shown in Table and Figures S19–S24. Based on the distance within these repeating features, D 2 and D 3 can be attributed to T-shaped and sandwich π–π stacking (combined parallel displaced and cofacial parallel stacked) interactions between the abundant lignin aromatic rings. , This should however be considered a simplification due to the highly complex three-dimensional lignin network structures. These π–π stacking interactions between aromatic rings normally play an important role in the stability of the systems and their properties. ,, It is however not clear how these internal stacking interactions scale when being imbedded into a larger structural ordering.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to stress that the aim of this work is not to derive new structures for WBDCs starting from randomly different configurations but rather to corroborate that there may be structures whose geometries are like those estimated with MD simulations 26 trapped in a nearby local minimum of energy landscapes estimated with DFT calculations.…”
Section: Computational Methodologymentioning
confidence: 95%
“…2 by removing -OCH 3 groups). 26 Thus, to obtain the methoxylated complexes SÁ Á ÁG and SÁ Á ÁS, one and two -OCH 3 groups were introduced into G units, respectively. This study was performed for simple lignin complexes having a high content of -OCH 3 in their units because the S-unit shows less crosslinking in the native lignin's network.…”
Section: Optimization Of Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin Builder is another robust tool that can be used to construct lignin structures and study interaction with other components (Figure b) . Many authors have used this software to model lignin structures and understand their properties and behavior. …”
Section: Atomistic Representations and Chemistry Of Lignocellulosic M...mentioning
confidence: 99%